Bioengineering an AI-augmented platform for remote mental health interventions - Ju Yu Wu; Yu-Jie Chen; Yen-Feng Lin; Congo Tak Shing Ching; Hui-Min David Wang; Yi-Chung Chen; Yang-Chou Juan; Lun-De Liao (Results in Engineering)
This study developed and tested a new teletherapy system that uses artificial intelligence (AI) to improve remote psychological treatment and reduce therapists’ workload. The system includes a case management platform and a video-based therapy platform with support for remote Eye Movement Desensitization and Reprocessing (EMDR). After each session, the system uses AI tools such as emotion recognition, speech-to-text, and a large language model to automatically create a session summary and report, including emotional changes and a transcript. Real-time eye movement tracking and distance monitoring help standardize remote EMDR procedures. The case management system improves efficiency by helping schedule sessions and reminding clients (rated 4.25±0.83 out of 5). In clinical trials, AI-generated summaries reduced report writing time by over 50 %. Less experienced therapists found the emotion recognition tool helpful for self-reflection (4.3 ± 0.64), while experienced therapists believed the EMDR tools improved their remote consultation skills (4.2 ± 0.75). User feedback shows the system is easy to use, with therapists rating it 4.83 and clients 4.33 for ease of use. Overall, the system improves access to mental health services, increases workflow efficiency, and supports professional development in digital therapy.